Pengaruh Adversity Intelligence terhadap Kecemasan Menghadapi Tantangan Mencari Pekerjaan Kondisi Pandemi Covid-19 - Adila Fitri Cahyani; Ahyanuardi Ahyanuardi (Jurnal Pendidikan Teknik Elektro, 2022)
This study aims to determine the Effect of Adversity Intelligence on Anxiety faced with the Challenge of Finding a Job during the COVID-19 pandemic condition in Electrical Engineering Education Students. This type of research is quantitative, so the data in the form of numbers is analyzed using statistics. This quantitative research uses a correlational approach. The subjects in this study were students of the Electrical Engineering Education study program at Padang State University who were in their final semester, namely students of the 2018 class, with a total of 34 respondents. This research instrument is in the form of a questionnaire that has gone through a validation process by expert lecturers from the Department of Electrical Engineering and the instrument testing process. Validity and reliability tests were carried out after the instrument testing process was completed. Data collection is done by distributing questionnaires to respondents online, namely through a Google form. The data analysis technique used a simple linear regression test to predict the influence of the independent variable, namely adversity intelligence, on the dependent variable, namely anxiety. Hypothesis testing in this study used the T-test. Studies indicate that adversity intelligence had a negative and significant effect on anxiety facing the challenge of finding work in the COVID-19 pandemic conditions in students of the Electrical Engineering Education study program.